Dakwah digital sebagai sarana peningkatan pemahaman moderasi beragama dikalangan pemuda - Fathurrrahman 'Arif Rumata; Muh. Iqbal; Asman Asman (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2021)
Digital da'wah was chosen to be one of the solutions in increasing understanding of religious moderation, giving a new color in world da'wah. Its effectiveness and easy access are the reasons for the existence of da'wah through digital. but behind the conveniences offered there are difficulties and challenges that must be faced. Lack of wisdom in the use of technology often has a serious impact on users. For example, the emergence within among others to the decline in awareness of moderation in religion. This paper wants to examine how big the impact of digital da'wah is in increasing the understanding of moderation in religion among youth, as well as how the etiquette is in digital da'wah. This research data is sourced from digital literature such as online news, journals, websites, online documents. The collected data is then reduced and constructed into a whole and fresh new concept. Data analysis was carried out using content analysis with intertextuality and meaning of creativity. The results of the study show that generational familiarity with social media opens up great opportunities for severe preachers, especially from the youth in spreading da'wah content digitally. This is very supportive in conveying the importance of religious moderation in order to prevent conflicts that arise in the life of a heterogeneous society.***Dakwah digital dipilih menjadi salah satu solusi dalam meningkatkan pemahaman moderasi beragama telah memberikan warna baru dalam dunia dakwah. Efektivitas dan mudahnya akses menjadi alasan eksistensi dakwah melalui digital. namun dibalik kemudahan-kemudahan yang ditawarkan ternyata terdapat kesulitan-kesulitan dan tantangan yang harus dihadapi. Kurang bijaknya dalam penggunaan teknologi kerapkali menimbulkan dampak serius bagi para user. Misalnya, timbulnya intoleran antar sesama sampai turunnya kesadaran akan moderasi dalam beragama. Tulisan ini ingin menguji seberapa besar dampak dakwah digital dalam meningkatkan pemahaman moderasi dalam beragama di kalangan pemuda, serta bagaimana adab-adab dalam berdakwah digital. Data penelitian ini bersumber dari literatur digital seperti, berita online, jurnal, website, maupun dokumen-dokumen online. Data-data yang terkumpul, kemudian direduksi dan di konstruksi menjadi konsep baru yang utuh dan fresh. Analisis data dilakukan dengan menggunakan analisis isi yang mengedepankan intertextualities dan meaning creativity. Hasil penelitian menunjukkan bahwa Keakraban generasi mudah dengan media sosial membuka peluang yang besar bagi parah pendakwah khususnya dari kalangan pemudah dalam menyebarkan konten dakwah secara digital. Hal ini sangat mendukung dalam penyampaian tentang pentingnya moderasi beragama guna mencegah konflik yang muncul dalam kehidupan masyarakat yang heterogen.